Psikososial dan Beban Kerja Perawat – Sebuah Penelitian di Salah Satu RS Militer di Indonesia - Hardianto Iridiastadi; Vera Septiawati; Euis Nina Saparina Yuliani; Hernadewita Hernadewita (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
This study aimed to determine the level of mental workload and psychosocial factors of nurses at the executive level in in-patient rooms of a military hospital. Data were collected by distributing questionnaires to 41 nurses who served in the in-patient rooms. Measurement of mental workload was carried out using the National Aeronautics and Space Administration - Task-Load Index (Nasa-TLX) questionnaire. Measurement of psychosocial factors was carried out using the Copenhagen Psychosocial Questionnaire (COPSOQ II) questionnaire. The results showed that the average value of the overall mental workload was in the high category. The value of psychosocial factors in the work environment shows good results on the majority of the rating scales. However, the hospital needed to pay attention to several factors, such as emotional demands, health perceptions, fatigue and stress and work pace. The results of this study also showed a strong and significant positive relationship between the dimensions of management's trust and performance with r=0.545(p=0.000). Thus, it is recommended that hospital management not only assess the performance of nurses, but also periodically assess mental workload and psychosocial factors in order to create a conducive work environment